Determination of safety margin of nasal septum osteotomy for sphenoid sinus in cleft lip and palate patients - Ergin Ozturk; Gorkem Tekin; Nesrin Saruhan Kose; Mehmet Ugurlu; Elif Bilgir; Omur Dereci (BMC, 2024)
Abstract Background Nasal septum osteotomy is used for separating the nasal septum and maxilla during a Le Fort I osteotomy. If this osteotomy is applied too high or is tilted into the nasal cavity, the sphenoid sinus and various adjacent vital structures may be damaged, and serious bleeding, neurological complications, blindness or even death may occur. The aim of this study is to determine the safety margin of the nasal septum osteotomy for sphenoid sinus during the Le Fort I surgery in cleft lip and palate (CLP) patients. Methods Twenty cleft lip and palate (the CLP group) and 20 healthy individuals (the control group) were included in this study. Three values (two lines and an angle) were measured by cone beam computed tomography (CBCT). The first line is the line passing through the junction of the spina nasalis anterior point and the lower point of the perpendicular lamina of the palatine bone. The undersired line is the line passing through the junction of the spina nasalis anterior point and the lower anterior border of the base of the sphenoid sinus. The osteotomy angle is the angle between these two lines. Results In the control group; a surgical line of 44.11-61.14 mm (mean 51.91 ± 4.32), an undesired line of 52.48-69.58 mm (mean 59.14 ± 5.08) and an angle of 18.22-27.270 (mean 22.66 ± 2.55) were found, while in the CLP group, a surgical line of 34.53-51.16 mm (mean 43.38 ± 4.79), an undesired line of 46.86-61.35 mm (mean 55.02 ± 3.24) and an angle of 17.60-28.810 (mean 22.60 ± 2.81) were found. Conclusions Although the angle to the sphenoid sinus was not significantly affected by CLP, careful planning and consideration of these anatomical differences are crucial to prevent complications and ensure the safety of Le Fort I surgery in CLP patients. Further research with larger sample sizes and subgroup analysis of unilateral and bilateral CLP cases is needed to improve our understanding of these anatomical variations and improve surgical approaches to individuals with CLP undergoing orthognathic procedures.